EFEKTIVITAS PIJAT PERINEUM TERHADAP KEJADIAN RUPTUR PERINEUM PADA PERSALINAN SPONTAN PRIMIGRAVIDA - Yuliani Tangko; Asrawaty Asrawaty; Ida Ariyanti; Noviyati Rahardjo Putri; Isnu Kurnia (Midwifery Care Journal, 2021)
Perineal rupture cases in Indonesian occur in women at the age of 25-30 years are 24%, while at the age of 32-39 are 62%. Perineal rupture can cause female organ dysfunction, bleeding, and infection. One way to prevent perineal rupture is to do perineal massage to increase blood flow and elasticity of the perineal. This study aims to analyze the effect of perineal massage on the incidence of spontaneous perineal rupture in primigravida normal deliveries. This research method uses a literature review by conducting searches on the PubMed, Science Direct, and Google Scholar databases. The literature used is written in English and Indonesian. The articles in this study were published in 2014-2018. The keywords used are Perineal Massage, Rupture Perineum, and Primigravida Normal Labor. From the 12 articles which had been obtained, 8 articles discuss the benefits of perineal massage to prevent perineal rupture, 1 article discusses the comparison of perineal massage with kegel exercise, 1 article discusses risk factors that can affect the occurrence of perineal rupture, 1 article discusses knowledge and the period of service of the midwife related to perineal massage and 1 article discusses perineal massage which does not provide benefits to perineal rupture but perineal massage is safe during delivery. Perineal massage can increase the elasticity of the perineal muscles, relax the perineal tissue, prevent perineal tears, facilitate the delivery process so that labor complications do not occur, and reduce maternal morbidity